Determination of local mesh parameters in finite element problems - Bakulin, Vladimir Nikolaevich; Inflianskas, Vatslovas Vatslovovich (Computational Continuum Mechanics, 2013)
Two basic cases of convergence of finite element solution in the static problems of the theory of elasticity are considered. Based on Saint-Venant’s principle, the sufficiency of finite element mesh refinement for local regions with stress concentration is determined. An algorithm is presented for evaluation of point-by-point convergence of solution for local mesh refinement. To illustrate the method, the results of computation of a cylindrical three-layered composite shell under local loads are given. For stresses reaching the maximum value in the loaded area, the mesh density parameters yielding an initial approximation are found.
Keywords: finite element method; numerical solutions; convergence evaluation; problems of mechanics of laminated shells; stress concentration; finite element mesh; variable mesh density